IMPLEMENTATION OF OUTCOME BASED EDUCATION (OBE) CURRICULUM ON THE QUALITY OF ACCOUNTING DIPLOMA GRADUATES AT ACEH POLYTECHNIC - Hilmi; Rizki Ramadhan; Meutia Handayani; Ardian; Dewi Maya Sari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The implementation of the Outcome-Based Education (OBE) curriculum in the D3 Accounting Study Program is an effort to prepare graduates with skills relevant to the current job market needs. This study aims to analyze the implementation of the OBE curriculum in the program, focusing on skills that support job readiness, such as critical thinking, effective communication, collaboration, and creativity. The research method used is a qualitative approach with data collection techniques through observation, interviews, and document studies. The research results indicate that the implementation of the OBE curriculum has increased the relevance of learning to the demands of the workforce, but still faces challenges such as limited resources and the need to expand collaboration with external parties. These findings indicate that the OBE curriculum is effective in equipping students with the practical skills needed in Industry 5.0, while also developing their academic and professional potential. The implications of this research are expected to serve as a reference for other educational institutions in implementing the OBE curriculum, particularly in the D3 Accounting Study Program.bstract also written in English containing key issues, objectives, methods and results. Abstract written in a single paragraph is, no more than 200 words. (Times New Roman 11, single space, and italics).